Constructions of ideal lattices with full diversity - Andrade, Antonio Aparecido de [UNESP]; Carvalho, Edson Donizete de (Institute of Advanced Scientific Research, 2011)
In this paper, we present new constructions of ideal lattices for the Rayleigh fading channel in Euclidean spaces with full diversity. These constructions are through totally real subfields of cyclotomic fields, obtained by endowing their ring of integers. With this method we reproduce rotated versions of algebraic lattices where the performance in terms of minimum product distance is related with the field determinant.
Keywords: cyclotomic field; ideal lattice; Diversity; minimum product distance